Investigation of space-time signals statistics in optoelectronic systems - Стрелкова, Т.А.Стрелкова; Созонов, Ю.И.; Яновский, Ю.А. (Radiotekhnika, 2012)
Statistical analysis of signal and background components of an image is investigated with the aim of random value distribution law determination. The approximating function of the stochastic signal distribution law in the process of space-time transformation in optoelectronic systems is found. It allows using the known distribution parameters for a random value description and images transformations algorithm optimization.